Language Policy and the Construction of National Identity in Colombia (Encuentros, 2018)
The connection between identity and language is hard to deny. In the production of national identities, language plays a key role in the homogenizing of the population by political will. Since the conquest of Colombia over 500 years ago, language has been a crucial tool in the construction of national identity and the concept of nation. This article, through archival research, critical reading, textual analysis, and grounded theory, examines the role of language from pre-colonial Colombia to modern day Colombia in the formation of national identity and character. It carefully and critically examines the roles and conflicts of Spanish and indigenous languages in colonial laws until modern education legislation, and the current rise of English in education law, and what this means in terms of national identity for Colombia.
Keywords: national identity; language policy; language education; identity theory